PENGARUH PENGUKURAN TEKANAN DARAH TERHADAP PERUBAHAN ANSIETAS PADA KLIEN HIPERTENSI DI DESA KOBO KECIL KOTAMOBAGU TIMUR - Kanine, Esrom; Paputungan, Sriwintari (JURNAL KEPERAWATAN, 2018)
Abstrac: Background:Hypertension includes cardiovascular diseases that can affect the work activity of the heart.The among hypertension patients was in Kobo Kecil is 229 poeple. The results of the surveydata describe feelings of anxiety often felt by patients with hypertension both who regularlycheck blood pressure. Aims: This study was conducted to analyze the influence bloodpressure measurement for anxiety changes in hypertensive patients. Methods: This researchusing the design of quantitative research. Thirty four samples were recruited using purposivesampling strategy, using quasi experimental pre-test and post-test without control group.Some including age 30-55 year old, The level of anxiety was measured by Hamilton AnxietyRating Scale. Data was analyzed using paired t test, with p value < 0,05. Result : The meananxiety levels different before and after intervention were 1.32 to 2.35.00 (Paired t test equalto – 1.02 and p value = 0.000). Conclusion : This findings describes significance of theinfluence blood pressure measurement for anxiety changes in hypertensive patientsKeywords :blood pressure measurement, Anxiety, Hypertensive patients